Identification of Heavy Metal in Palm Oil Empty Fruit Bunch Compost, Mulch from Palm oil Waste and Its Effect on Chili (Capsicum annuum L.) - Mercy Bientri Yunindanova; Herdhata Agusta; Dwi Asmono (Indonesian Journal of Physics and Nuclear Applications, 2016)
This study aimed to investigate the effect of compost from oil palm empty fruit bunches with different ages, mulching oil palm waste, the levels of heavy metals in compost and its influence on the growth and yield of chili. Composting was assisted by the starter (PromiTM) with a dose of 0.5 kg per ton of chopped bunches. Composting treatment distinguished by the composting time namely 4, 6, 8 and 10 weeks. Mulch treatment consisted of shell, fiber and empty fruit bunch chopped. The empty fruit bunch compost had the potential to decrease the soil acidity because the pH of 7.89- 8.66. The EFBs compost contained Boron of 7.7-10.7 ppm, 12-24.8 ppm of Cuprum, 0.05 to 0.24 % of Fe, 26.5-89.7 ppm of Mn, and 9.1-10.8 ppm of Na. This compost contained heavy metal Cd and Hg. Cd was detected in amount of 0.08 to 0.25 ppm. Hg was detected in amount of 12.9-19.5 ppm. Meanwhile, Pb and As were not found. Cd did not exceed the threshold. On the other hand, Hg was detected exceeding the threshold but did not affect the growth and yield of chili. Organic mulch from palm oil wastes did not significantly affect on the chili yield. Shell mulch had a negative influence on the growth and yield of chili.